(untitled) (World Science, 2022)
Recurrent vulvovaginal candidiasis (RVVC) is a widespread problem for today. Symptoms of the disease significantly reduce women life quality. It is common reason for medical help. Clinical sings of vaginal candidiasis are nonspecific. The most common method of diagnosis - microscopy of vaginal discharge, does not always provide enough information. Among the causative agents of candidiasis, Candida albicans and Candida nonalbicans have different prevalence in different regions of the world. Resistance to antifungal drugs is increasing due to it widespread applying. Risk factors for RVVK are: antibiotic therapy, immunodeficiency conditions, diseases of the gastrointestinal tract, contraceptives, corticosteroids, hormonal disorders of women, allergic diseases. Recent studies indicate the multifactorial cause of candidiasis, especially the imbalanced composition of the vaginal microflora and genetic predisposition. Resistance to antifungal drugs is increasing, especially to Fluconazole, that is most often applied in clinical practice. The role of immunoregulatory mechanisms is reflected in the reduced activity of immunity in the vagina. Changes in Tol-like receptor (TLR) genes have been reported in women with RVVC. Also, interlexins can lead to a prolonged inflammatory process in the vagina. Currently, polymorphism of the mannose-binding lectin gene in women with RVVK relevant topic for research. That changes may be a reasone of recurrence. Determination of mannose-binding lectin for diagnostic and therapeutic purposes is promising research area. There is increasing scientific interest in the study of this pathology. In publication described diagnosis of RVVK, the species composition of the pathogen, risk factors, impact of hormones and genetic predisposition.